1992
DOI: 10.1002/ffj.2730070604
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Flavour Constituents of Chempedak (Artocarpus polyphema Pers.) Fruit and Jackfruit (Artocarpus heterophyllus Lam.) from Malaysia

Abstract: Steam-distilled volatile constituents from chempedak (Arfocarpus polyphemaPers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…Among all odorants identified using GC-MS on two different columns, 4-hydroxy-2,5-dimethyl-3(2H)-furanone (sweet, burnt sugar-like) had the highest FD factor followed by ethyl 2-methylbutanoate, ethyl 3-methylbutanoate, 3-methylbutanal, 3-(methylthio) propanal, 3-methylbutanoic acid, and 2-acetyl-1-pyrroline (tentative identified). Except for ethyl 2-methylbutanoate, all of the above compounds had been previously identified in chempedak fruit (Wong et al, 1992). However, ethyl 2-methylbutanoate which contributes fruity note was reported as Oily, fresh and floral aromatics associated with coconut-oil 9.1 Fruity Sweet, fruity, berry-like aromatics associated with blend of fruits 8.0 the major volatile compound in several tropical fruits such as durian (Voon, Sheikh Abdul Hamid, Rusul, Osman, & Quek, 2007), jackfruit (Ong et al, 2008) and pineapple (Pino, 2013).…”
Section: Aroma-active Compoundsmentioning
confidence: 92%
See 3 more Smart Citations
“…Among all odorants identified using GC-MS on two different columns, 4-hydroxy-2,5-dimethyl-3(2H)-furanone (sweet, burnt sugar-like) had the highest FD factor followed by ethyl 2-methylbutanoate, ethyl 3-methylbutanoate, 3-methylbutanal, 3-(methylthio) propanal, 3-methylbutanoic acid, and 2-acetyl-1-pyrroline (tentative identified). Except for ethyl 2-methylbutanoate, all of the above compounds had been previously identified in chempedak fruit (Wong et al, 1992). However, ethyl 2-methylbutanoate which contributes fruity note was reported as Oily, fresh and floral aromatics associated with coconut-oil 9.1 Fruity Sweet, fruity, berry-like aromatics associated with blend of fruits 8.0 the major volatile compound in several tropical fruits such as durian (Voon, Sheikh Abdul Hamid, Rusul, Osman, & Quek, 2007), jackfruit (Ong et al, 2008) and pineapple (Pino, 2013).…”
Section: Aroma-active Compoundsmentioning
confidence: 92%
“…but is smaller and has a softer flesh. At its mature state, chempedak has a strong unique aroma which is preferable among consumers in those regions (Chong et al, 2008;Wong, Lim, & Wong, 1992). Moreover, chempedak flavor has been reported similar to durian (Nakasone & Paull, 1998).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Rasmussen (1983) reported 21 compounds with similar extract composition. Wong, Lim, and Wong (1992) analyzed the steam-distilled volatile constituents from fruits grown in Malaysia by capillary GC and GC/MS, revealing 45 volatile components of which 32 have not been reported previously. The authors Table 2 The main compounds found in Acerola (Malpighia sp.)…”
Section: Jackfruit (Artocarpus Heterophyllus L)mentioning
confidence: 99%